(untitled) (Issues in Social and Environmental Accounting (ISEA), 2013)
This research aims to take steps towards explaining behavioral principle-based board process as factors for effective board performance. Dominant rule-based board structure approach could not transform effective corporate functioning, thus inconclusive. Based on a survey perception of 154 respondents from Nigerian capital market participants, the study employs confirmatory factor analysis (CFA) in a structural equation modeling (SEM) approach. Other studies used EFA and in developed nations. Replicates and builds upon board process constructs - cognitive conflict, effort norms, use of knowledge and skills, and groupthink. The study concludes that the items are valid measures of the latent constructs and significantly relate to board perform ance. The paper links corporate governance debates to broader behavioral choices in agency perspective and employs CFA and SEM as alternative approach for the measurement and struc tural models, in place of the usual exploratory factor analysis (EFA).